2012
DOI: 10.1021/ja3101566
|View full text |Cite
|
Sign up to set email alerts
|

Total Structure and Optical Properties of a Phosphine/Thiolate-Protected Au24 Nanocluster

Abstract: We report the synthesis and total structure determination of a Au(24) nanocluster protected by mixed ligands of phosphine and thiolate. Single crystal X-ray crystallography and electrospray ionization mass spectrometry (ESI-MS) unequivocally determined the cluster formula to be [Au(24)(PPh(3))(10)(SC(2)H(4)Ph)(5)X(2)](+), where X = Cl and/or Br. The structure consists of two incomplete (i.e., one vertex missing) icosahedral Au(12) units joined by five thiolate linkages. This structure shows interesting differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
273
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 229 publications
(283 citation statements)
references
References 44 publications
8
273
1
1
Order By: Relevance
“…3 (36) Au22(dppo)6 (37) Au14(PPh3)8(NO3)4 (35) [Au24(PPh3)10(SC2H4Ph)5] + (38) [Au25(PPh3)10(SEt)5] 2+ (39) [Au39(PPh3)14Cl6] 2+ (40) appears to assist the holding of the cluster skeleton. [79]. The Au-Au bond distances in these icosahedron-based clusters (36)(37)(38)(39) are similar to those of smaller centered clusters, being in the range 2.63-3.23 Å ( Table 2).…”
Section: Higher-nuclearity Clustersmentioning
confidence: 58%
See 1 more Smart Citation
“…3 (36) Au22(dppo)6 (37) Au14(PPh3)8(NO3)4 (35) [Au24(PPh3)10(SC2H4Ph)5] + (38) [Au25(PPh3)10(SEt)5] 2+ (39) [Au39(PPh3)14Cl6] 2+ (40) appears to assist the holding of the cluster skeleton. [79]. The Au-Au bond distances in these icosahedron-based clusters (36)(37)(38)(39) are similar to those of smaller centered clusters, being in the range 2.63-3.23 Å ( Table 2).…”
Section: Higher-nuclearity Clustersmentioning
confidence: 58%
“…The spectra of higher-nuclearity centered clusters (36)(37)(38)(39) taken from the literatures [66,73,79,85] are summarized in Fig. 6b.…”
Section: Absmentioning
confidence: 99%
“…[25][26][27][28][29][30][31][32][33][34] A key challenge remaining for silver NCs is obtaining highly anisotropic shapes. In gold, NCs of anisotropic shapes were reported through solely thiols 35,36 and co-ligands of phosphines and thiols 37,38 . Such a strategy of co-ligands in sliver has failed to produce analogous results.…”
Section: Introductionmentioning
confidence: 99%
“…Aikens, et.al studied the structural, electronic and optical properties of the thiolate-protected Au 38 (SR) 24 (R=CH 3 and C 6 H 13 ) cluster (40) and the origin of discrete optical absorption spectra of Au 25 (SH) 18 - 60 cluster with an icosahedral Au 114 core with 30 RS-Au-SR units as ligand and yielded an excellent fit of the structure factor to the experimental X-ray scattering structure factor (42). The optical absorption spectrum of Au 24 nanocluster protected by the mixed ligands of phosphine and thiolate was theoretically reproduced and interpreted (43). Most interestingly, ultrafast luminescence dynamics of thiolate protected Au 25 clusters indicated that their luminescence decay traces showed unique ultrafast growth and decay kinetics that are absent in the larger Au clusters (44).…”
Section: Introductionmentioning
confidence: 85%